2017
DOI: 10.1103/physrevapplied.7.034018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Mott-Schottky Measurements under Illumination in Organic Bulk Heterojunction Solar Cells

Abstract: The Mott-Schottky analysis in the dark is a frequently used method to determine the doping concentration of semiconductors from capacitance-voltage measurements, even for such complex systems as polymer:fullerene blends used for organic solar cells. While the analysis of capacitance-voltage measurements in the dark is relatively well established, the analysis of data taken under illumination is currently not fully understood. Here, we present experiments and simulations to show which physical mechanisms affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…It was already reported that the current is significantly lesser than the saturation current at low voltages, but the current was restricted to the saturation current at the contact at high voltages [ 59 ]. The lower value of the built-in potential (Vbi), obtained from the Mott-Schottky plot under illumination, can be ascribed to the capacitance originating from the photogenerated charge carriers that can build up in the low-mobility materials, even at reverse bias [ 60 ]. When doping concentration increases, charge accumulation increases at the interface and the capacitance value will also rise.…”
Section: Resultsmentioning
confidence: 99%
“…It was already reported that the current is significantly lesser than the saturation current at low voltages, but the current was restricted to the saturation current at the contact at high voltages [ 59 ]. The lower value of the built-in potential (Vbi), obtained from the Mott-Schottky plot under illumination, can be ascribed to the capacitance originating from the photogenerated charge carriers that can build up in the low-mobility materials, even at reverse bias [ 60 ]. When doping concentration increases, charge accumulation increases at the interface and the capacitance value will also rise.…”
Section: Resultsmentioning
confidence: 99%
“…18 By conducting the measurements in the dark, where the mobility of the carriers does not affect the device electrostatics, we can establish the depletion region caused by unintentional doping rather than a mobility imbalance. 17,18 The results of the capacitance-voltage experiments in the dark and the Mott-Schottky plots for the 100-nm and 300-nm devices, along with the derivative doping profiles across the active layer width are demonstrated in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements were performed in the C p mode. 17 The performance of the devices was tested both prior to and after the C-V measurements with no sign of degradation. Mobility measurements.…”
Section: Characterizationmentioning
confidence: 99%
“…Mott-Schottky analysis on thick devices has been performed according to ref [3][4][5][6][7] . This analysis is based on the understanding that the depletion width at a semiconductor-metal contact changes with variation in the reverse bias potential.…”
Section: Mott-schottky Analysismentioning
confidence: 99%